2020
DOI: 10.3390/cells9051221
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans Induces Autophagy in Human Junctional Epithelium Keratinocytes

Abstract: The adverse environmental conditions found in the periodontium during periodontitis pathogenesis stimulate local autophagy responses, mainly due to a continuous inflammatory response against the dysbiotic subgingival microbiome. The junctional epithelium represents the main site of the initial interaction between the host and the dysbiotic biofilm. Here, we investigated the role of autophagy in junctional epithelium keratinocytes (JEKs) in response to Aggregatibacter actinomycetemcomitans or its purified lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…20 In addition, the junctional epithelium migrates apically resulting in the formation of a deep periodontal pocket as periodontitis advances. 25 YNBY improved the attachment site of the newly formed junctional epithelium and the renewal of the underlying connective tissue. In addition, the shape of the dental papilla was partially restored, indicating that YNBY exhibits positive effects on alveolar bone regeneration and soft tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, the junctional epithelium migrates apically resulting in the formation of a deep periodontal pocket as periodontitis advances. 25 YNBY improved the attachment site of the newly formed junctional epithelium and the renewal of the underlying connective tissue. In addition, the shape of the dental papilla was partially restored, indicating that YNBY exhibits positive effects on alveolar bone regeneration and soft tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…As an innate immune response mechanism, autophagy has been shown to be involved in the elimination of some intracellular pathogens, such as Salmonella Typhimurium [ 25 ], Mycobacterium tuberculosis [ 26 ], and Aggregatibacter actinomycetemcomitans [ 27 ]. However, studies have shown that some pathogens have evolved molecular strategies to manipulate the autophagic process for their own benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial effect of 1,25D3 greatly decreased after autophagy inhibition with 3-methyladenine (3-MA) treatment [ 65 ]. A. actinomycetemcomitans infection induced autophagy in human junctional epithelium keratinocytes (JEKs); this process inhibits the intracellular survival of the bacteria and significantly reduces the number of JEKs undergoing cell death [ 77 ]. 1,25D3 treatment enhances antibacterial activity to decrease the number of viable colonies of A. actinomycetemcomitans in cultured GEC [ 19 ].…”
Section: Possible Role Of 125d3 Via Autophagy Modulation In Periodont...mentioning
confidence: 99%